Integration of a StatCom and battery energy storage. - Yang, Z.
The integration of an energy storage system, such as battery energy storage (BESS), into a FACTS device can provide dynamic decentralized active power capabilities and much needed flexibility for mitigating transmission level power flow problems. This paper introduces an integrated StatCom/BESS for the improvement of dynamic and transient stability and transmission capability; compares the performance of the different FACTS/BESS combinations, and provides experimental verification of the proposed controls on a scaled StatCom/BESS system
Keywords: FACTS device; StatCom; Battery energy storage; Control system synthesis; Dynamic decentralized active power capabilities; Power system dynamic stability; Power system transient stability; Transmission capability; Transmission level power flow mitigation